Perceptions and Use of Safe Sleep Baby Boxes at Hospital Discharge by New Mothers. Issue 1 (January 2023) - Hughes, Kimberly; Gill, Sara L.; Berndt, Andrea
Abstract: Background: A large community hospital in South Texas began distributing safe sleep baby boxes to reduce sudden unexplained infant death (SUID) in 2017. Purpose: To describe safe sleep practices among new mothers who received a safe sleep baby box at hospital discharge. Methods: An information sheet containing a link to an online survey was mailed to all women who received a safe sleep baby box prior to discharge from the hospital from January 2018 to January 2019. Results: N = 84 women participated. Most reported using the safe sleep baby box only during nap time ( n = 62, 88.6%). Only 70.2% of participants reported that baby always slept their back ( n = 59). Most reported their baby did not use a pacifier ( n = 62, 73.8%), and many reported they were not breastfeeding their baby ( n = 38, 45.2%). Clinical Implications: Many women were not using the safe sleep baby box as intended and were not following many of the other safe sleep guidelines. Nurses should ask their patients about plans for infant safe sleep after discharge to provide individualized education or recommend specific resources to address the family's needs. Abstract : Safe baby sleep boxes were given to women on discharge from the hospital after childbirth. Researchers analyzed how and when the safe baby sleep boxes were used via survey during postpartum. Most women were not using the safe sleep baby box as intended and were not following many of the other safe sleep guidelines. Nurses should ask about plans for infant safe sleep prior to hospital discharge and provide individualized education and recommendations for specific resources to address the family's needs.